Managing Emissions for Climate Sustainability in Azerbaijan: Identifying Challenges and Proposing Solutions - Hasanova, Leyla; Fatdai, Saba; Muradova, Javahir (ADA University, 2024)
The topic of this capstone paper is to investigate the problems experienced by Azerbaijan in the sustainable management of emissions and implementation of policies towards climate sustainability. Therefore, these issues are going to be explored, followed by some policy recommendations. Environmental protection represents Azerbaijan's plan to encourage a green economy via initiatives, such as building green energy zones and increasing renewables capacity to 30% by 2030. However, the country faces several challenges that impede the greening process. The paper identifies three key problem areas: 1) lack of institutional and technical capacity for emissions management systems, 2) obstacles arising from oil/gas-based economy transformation to green growth, and 3) an insufficient legal framework in terms of both complying with international climate commitments (e. g. The Paris Agreement) and ensuring sustainable development. To tackle these problems, the paper proposes three policy alternatives: blending environmental education across public school programs, creating a favorable environment for renewable energy development and compensations, and establishing a national lowemissions strategy. Addressed alongside this issue would be capacity building to equip individuals with the technical skills and institutions with the required knowledge for efficient emissions management. Investor funds would be more responsive towards renewable by virtue of such financial incentives, where the transition from fossil fuels would rapidly take place. The creation of a national low emissions strategy, which international best practices can guide, can assure that clear and specific emission reduction targets are drawn and agreed upon based on global commitments. These policies would be quite helpful for Azerbaijan in terms of overcoming the problems mentioned above and enabling the country to realize the ways to achieve sustainable growth. Funding an educational program encompassing climate literacy, renewable incentives, energy, and a policy that stresses the necessity of low emissions nationwide will not only cut down emissions but also help diversify the economy and enable resilience and sustainable development goals.
Keywords: Sustainable development -- Azerbaijan.; Environmental policy -- Azerbaijan.; Climatic changes -- Government policy -- Azerbaijan.; Renewable energy sources -- Government policy -- Azerbaijan.; Green economy -- Azerbaijan.; Energy transition -- Economic aspects -- Azerbaijan.